Perancangan UI/UX Aplikasi BelPython Berbasis Android Menggunakan Metode Design Thinking (Current Research in Education: Conference Series Journal, 2023)
Designing UI/UX application requires careful concern, because later it will be the key of the message contained in the application can be conveyed to the user or not. BelPython is an application to learn basic python programming language based on android, python programming language is currently popular and ranked first in PYPL (Popularity of Programming Language) and many people want to learn python programming language for free and can be done on mobile. From the problems above, it can provide an opportunity to be able to develop an application that can be a source of learning the python programming language and can be accessed anywhere and anytime for free. This study uses a qualitative approach by applying the design thinking design method. The results of the study found that the UI/UX of the application so far has fulfilled the user's needs for using the BelPython application. It can be concluded that by applying the design thinking method the author can find out user needs starting from the stage of getting user problems, analyzing problems, determining problem formulations, implementing ideas in an initial application design, and testing the initial designs made in developing a UI/UX on BelPython application.